In vitro propagation of Etlingera elatior (Jack) (torch ginger) - Yunus, Muhamad Fahmi; Abd Aziz, Maheran; Abdul Kadir, Mihdzar; Abdul Rashid, Azmi (Elsevier, 2012)
An efficient protocol for complete plant regeneration from suckers of Etlingera elatior (Jack) has been developed. The addition of N6-benzyl amino-purine (BAP) (0, 13.32, 22.20, 31.08, and 44.40 μM) to the culture medium comprising Murashige and Skoog (MS) basal salts, 3% sucrose, 0.4% Gelrite™ did not show any significant effects on percentage of shoot induction and mean number of shoots produced. Various concentrations of BAP (0, 13.32, 22.20, 31.08, and 44.40 μM), 6-furfurylaminopurine (kinetin) (0, 13.95, 23.25, 32.55, and 46.50 μM) and N6-(2-isopentenyl) adenine (2-iP) (0, 14.76, 24.6, 34.44, and 49.2 μM) were tested for shoot multiplication. BAP at all levels were found suitable for the multiplication of shoot. However, the low level of 13.32 μM BAP was chosen as the best concentration of BAP due to economic feasibility. The best root proliferation was observed on MS medium without plant growth regulator (PGR). Assessment of various potting media for acclimatization showed medium containing soil:sand:peat moss (1:1:1) produced high survival of plantlets, number of leaves produced per plant and the plant height. This protocol provides a basis for future studies on mutation induction, genetic engineering, and could be applied for large-scale multiplication of this valuable plant.